Deep vein thrombosis and pulmonary embolism in neurosurgical patients - Saringcarinkul, Ananchanok; Pinon, Pathomporn; Punjasawadwong, Yodying (Biomedical Sciences and Clinical Medicine, 2016)
Deep vein thrombosis (DVT) is a common complication reported in the neurosurgical population. Some cases of DVT are followed by pulmonary embolism (PE), which can be a serious cause of morbidity and mortality in the postoperative period. Signifi cant risk factors of DVT development in patients undergoing intracranial surgery have been reported. Therefore, screening methods for early detection, measures of prophylaxis and DVT treatment have been proposed and utilized widely. However, the controversy remains over whether a single method or combination of pharmacological and mechanical methods is more effective in preventing DVT, while minimizing surgical bleeding, which is a serious problem for neurosurgeons.